EVALUATION METHODOLOGIES FROM A CONSTRUCTIVIST PERSPECTIVE - Karina Eliana Castro Intriago; Lubis Carmita Zambrano Montes (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
Evaluation methodologies constitute the fundamental pillar in the process of teachinglearning, being the beneficiaries of this interaction the teacher and student. The main objective of this article is to identify the evaluation methodologies applied from a constructivist perspective, emphasizing the different types of evaluation that are closely related to each other. The results obtained from the analysis are presented by means of a documentary bibliographic review that compiled the necessary information and allowed the analysis and deduction of clear and pertinent criteria on the importance of knowing how to evaluate the student in the educational context in order to develop an objective and fair academic performance. qualitatively and quantitatively and their corresponding feedback. The results showed that by executing an authentic and performance evaluation, with correct decision-making, favorable results will be obtained in the actors immersed in the student training process.